2022
DOI: 10.3390/pharmaceutics14020357
|View full text |Cite
|
Sign up to set email alerts
|

Parietin Cyclodextrin-Inclusion Complex as an Effective Formulation for Bacterial Photoinactivation

Abstract: Multidrug resistance in pathogenic bacteria has become a significant public health concern. As an alternative therapeutic option, antimicrobial photodynamic therapy (aPDT) can successfully eradicate antibiotic-resistant bacteria with a lower probability of developing resistance or systemic toxicity commonly associated with the standard antibiotic treatment. Parietin (PTN), also termed physcion, a natural anthraquinone, is a promising photosensitizer somewhat underrepresented in aPDT because of its poor water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The 1 O 2 quantum yields of MPPa and all formulations were measured and compared using DPBF as a probe and MB as the standard. The 1 O 2 quantum yield was calculated according to the literature 35 , 36 . DPBF results demonstrated that all formulations of SLNs exhibited better 1 O 2 photogeneration than the MPPa solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 O 2 quantum yields of MPPa and all formulations were measured and compared using DPBF as a probe and MB as the standard. The 1 O 2 quantum yield was calculated according to the literature 35 , 36 . DPBF results demonstrated that all formulations of SLNs exhibited better 1 O 2 photogeneration than the MPPa solution.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 O 2 quantum yields of MPPa and all formulations were determined using DPBF as a probe and MB as the standard with that calculation of Eq. ( 7 ) 35 , 36 . ɸ Δ : singlet oxygen quantum yield, ɸ S Δ : singlet oxygen quantum yield of MB equal to 0.596, ɣ S Δ : photodynamic activity of MB, and ɣ Δ : photodynamic activity of specimen.…”
Section: Methodsmentioning
confidence: 99%
“…Hyp photodegradation in the cyclodextrin inclusion complex was significantly slower than in the free form. A host–guest structure can attenuate hydrolysis or photolysis of drugs by protecting them from reactive substances . This shielding effect may lead to lower availability and interaction of complexed Hyp molecules with the light source.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, more and more research has been conducted on the efficacy of aPDT against microbial infections. In this regard, a variety of photosensitizers have been evaluated on many different microorganisms [ 10 , 11 , 12 , 13 , 14 , 15 ]. Furthermore, the efficacy of aPDT was also evaluated against coronavirus disease 2019 (COVID-19), in preventing infections and treating infected patients [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%